Phenomenology of untouchability - Sarukkai, Sundar (2009)
This paper explores the philosophical foundations of untouchability through an analysis of the phenomenology of "touch". The sense of touch is unique in many ways; one such is the essential relation between touch and "untouch". Drawing on both Indian and western traditions, the paper begins by analysing the meaning of touch and then goes on to explore some meanings of "untouchable". It then concludes by pointing out the importance of untouchability within the Brahmin tradition and attempts to understand the process of supplementation which makes untouchability a positive virtue for the Brahmins and a negative fact for the Dalits. - Reproduced.
Keywords: Untouchables